MOTIF PENGGUNAAN SIMBOL RELIGIUSITAS MAHASISWA BERKOPYAH - Sanusi, Sanusi (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
This study aims to determine the logical reasons for each student's social actions based on certain motives in the use of religiosity symbols in the form of skullcaps in all daily activities on campus and the surrounding environment. This research is a descriptive-qualitative study that describes the trends of reasons and motives for the use of religiosity symbols in the form of kopyah for students qualitatively. The results of the study obtained a number of reasons and factors that underlie the encouragement of students to use kopyah on campus. The dominant tendency towards what is done by a kopyah user is the psychological motive of fulfilling the need for comfort for a santri, the preventive motive is encouragement to guard against all immoral acts and other sins; in the form of encouragement to follow what was exemplified by a cleric who became a role model as a form of piety of a santri. In this case, kopyah becomes a certain identity characteristic inherent in itself along with the practice of its religiosity.Keywords:Motif, Symbol, Religiosity, Kopyah